FAKTOR-FAKTOR YANG MEMBERIKAN KONTRIBUSI TERHADAP KEPATUHAN WAJIB PAJAK OJEK ONLINE (OJOL) DI JAKARTA - Theressa Meiyanti; Mulyani Mulyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
Tax is a mandatory contribution to the state that is owned by an individual or entity that is a force. Indonesian tax compliance level is still low shown by its low tax ratio. Motor Vehicles Tax is a tax on ownership or control of motorized vehicles. Taxpayer’s compliance is taxpayers' willingness to fulfill their tax obligations concerning regulations. This research used quantitative hypothesis testing. The data and information were retrieved from questionnaire results filled in by 100 Gojek taxpayer drivers. This research used the Likert scale, SPSS 20 software, Validity and Reliability, Classical Assumption Test, F-test, t-test, and R2 test. Therefore, it can be concluded that taxpayer’s knowledge and awareness have a positive effect on motorcycle taxpayer’s compliance. However, there is no evidence that the taxpayer’s level of income has effects on motorcycle taxpayer’s compliance.Keywords: Taxpayer Compliance, Taxpayer Awareness, Taxpayer Knowledge, Taxpayer’s Level of Income